Sexual dimorphism related to occlusal traits in Australian children - Ribeiro Daniela C; Dreyer Craig W.; Lähdesmäki Raija; Townsend Grant C (Sciendo, 2018)
The aim of the present study was to assess sexual dimorphism related to occlusal variables recorded from dental casts of Australian twins and to compare trends across primary (T1), mixed (T2) and permanent (T3) dentitions in the same individuals.